Effects of nutritional status and diet composition on fatty acid transporters expression in zebrafish (Danio rerio). (18th January 2019) - Wang, Yanliang; Meng, Ran; Xu, Xiaorong; Liao, Kai; Ran, Zhaoshou; Xu, Jilin; Cao, Jiayi; Wang, Yajun; Wang, Danli; Xu, Shanliang; Yan, Xiaojun
Abstract: This study investigated the expression of zebrafish ( Danio rerio ) fatty acid transporters, such as scavenger receptor CD36, plasma membrane fatty acid‐binding protein (FABPpm), and fatty acid transport protein family (FATPs), in responses to nutritional status and diet composition. For diet composition study, three isonitrogenous (43% crude protein) purified diets were formulated to contain 6%, 12% and 18% crude lipid levels. Meanwhile five isonitrogenous and isoenergetic purified diets were formulated to contain different lipid sources including fish oil (FO; rich in n ‐3 HUFA), palmitic acid (PA; rich in C16:0), olive oil (OO; rich in C18:1n‐9), sunflower oil (SO; rich in C18:2n‐6) or perilla oil (PO; rich in C18:3n‐3) as the sole lipid source. Results showed that liver CD36, FABPpm‐a, FABPpm‐b, FATP1‐a and FATP6, intestine CD36, FABPpm‐a and FABPpm‐b, and muscle CD36 and FATP1‐b were significantly increased during postprandial period. During starvation, liver CD36, FABPpm‐a, FABPpm‐b and FATP1‐a, intestine FABPpm‐a, FABPpm‐b, FATP4 and FATP6, and muscle FATP1‐b, FATP4 and FATP6 were significantly increased. The expression of some fatty acid transporters (including liver CD36 and FABPpm‐b, intestine FABPpm‐a, and muscle CD36, FABPpm‐a, FATP1‐a, FATP2 and FATP4) was up‐regulated by refeeding, while the expression of other fatty acid transporters (liver FABPpm‐a and intestine FATP1‐a, FATP4 and FATP6) was down‐regulated by refeeding. The expression of several fatty acid transporters (liver FATP2 and FATP4, and intestine CD36, FATP2 and FATP4) was significantly increased by high‐lipid diet, whereas CD36, FATP1‐b, FATP2 and FATP4 expression in the muscle were reduced by increasing dietary lipid level. Compared with FO group, the muscle of fish fed the diet with OO had a higher CD36 mRNA abundance, while the muscle of fish fed the diet with OO and PO had a higher FATP1‐b expression. Compared with the FO group, the hepatic FATP2 mRNA was significantly increased in the PA group, while the intestine FATP2 mRNA was significantly increased in the SO and PO groups. In addition, intestine FATP4 expression in the PA and OO groups was lower compared with the FO group. The results indicate that zebrafish fatty acid transporters play a central role in coordinating the mobilization of fuel substrates in responses to nutritional status and diet composition.